Wh-Constraints in Interlanguage Grammar of L2 Learners from the Perspective of Universal Grammar: A Case Study of First-Year English Majors at a University in Vietnam - Ta Le Minh Phuoc (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
In the field of Second Language Acquisition (SLA), researchers are more concerned with the cognitive processes that L2 (second language) learners undergo than with the surface-level structural properties of language. Chomsky (1980) proposed the theory of Universal Grammar (UG), which consists of a system of principles governing the universal properties of natural languages. He argued that UG enables a child to acquire their L1 (first language), but whether L2 learners undergo the same process as in L1 acquisition remains a key question. The present study aims to address this question by analyzing the underlying acquisition processes of wh-constraints in English among a group of L2 learners. It also seeks to understand their interlanguage grammar, which is consistent and unique. The study employed a case study approach alongside a quantitative method using an Acceptability Judgment Test. Participants included 29 first-year English majors at a university in Vietnam. The findings suggest that these L2 learners have limited access to UG during L2 acquisition but have acquired specific aspects of wh-constraints. Additionally, higher language proficiency appears to support better acquisition of these constraints. The study also offers pedagogical implications for EFL teachers regarding grammar teaching. Received 15th December 2024; Revised 15th March 2025; Accepted 15th April 2025